EFFECTIVE TEACHING OF PHRASEOLOGY IN THE COURSE OF UKRAINIAN AS A FOREIGN LANGUAGE: PRACTICAL APPROACHES - Zlotnyk-Shahina, Olha (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article examines the features of teaching phraseology in the course of Ukrainian as a foreign language, emphasizing the importance of developing students’ ability to understand and use phraseological units in various communicative situations. This is a crucial step in enhancing their linguistic competence, as phraseological expressions reflect the specific cultural and historical phenomena of a society, requiring a deeper understanding of not only the language itself but also the mental models of the community that uses it. The paper provides a detailed analysis of methodological approaches to teaching phraseology aimed at facilitating the acquisition of complex language units. These approaches include contextual analysis, creative exercises, game-based methods, and interactive tasks that make the learning process more effective and engaging, fostering active student participation in language activities. Special attention is given to the significance of cultural context in studying phraseology, enabling students not only to master linguistic units but also to gain a deeper understanding of the cultural, historical, and social aspects influencing the meanings of phraseological expressions. The article explores methods aimed at developing students’ critical thinking skills, such as analyzing and interpreting phraseological expressions in context. Suggested activities include creating dialogues, writing essays with active use of phraseological units, and working with authentic texts, which allow students to observe the practical application of phraseology in various speech situations. The study highlights the importance of cultural context in mastering phraseology, as it helps students understand not only the linguistic forms but also the cultural and historical dimensions of their meanings. At the same time, it emphasizes methods that foster critical thinking, enabling students to analyze and interpret phraseological expressions contextually. To achieve this, tasks such as creating dialogues, composing essays that incorporate phraseological expressions, and analyzing authentic texts are recommended, helping students see how phraseology is applied in real-life communication. Based on the conducted analysis, the article concludes that a comprehensive approach to teaching phraseology—encompassing cognitive, cultural, and interactive methods-not only effectively develops phraseological competence in students learning Ukrainian as a foreign language but also enhances their ability to acquire phraseological expressions, while promoting critical thinking skills and intercultural communication. _____________ References: • Azarova, V., Horchynska, L. V., & Pustovit, T. M. (2019). Osoblyvosti vyvchennia frazeolohizmiv u vykladanni ukrainskoi movy yak inozemnoi [Peculiarities of studying phraseological units in teaching Ukrainian as a foreign language]. Naukovyi visnyk Vinnytskoho natsionalnoho tekhnichnoho universytetu [Scientific Bulletin of Vinnytsia National Technical University]. Retrieved from https://ir.lib.vntu.edu.ua/bitstream/handle/123456789/28432/Azarova_2019S4.pdf • Zharko, (2019). Shliakhy ta zasoby formuvannia komunikatyvnoi kompetentsii pid chas vyvchennia inozemnoi movy v nemovnykh zakladakh vyshchoi osvity [Ways and means of developing communicative competence during foreign language learning in non-linguistic higher education institutions]. Molodyi vchenyi [Young Scientist], 2(66), 88–91. Retrieved from https://molodyivchenyi.ua/index.php/journal/article/view/2916 • Potiuk, Ye. (2016). Metodyka formuvannia inshomovnoi leksychnoi kompetentnosti studentiv v umovakh stratehichnoho vyvchennia inozemnoi movy (komunikatyvnyi aspekt) [Methodology for developing students’ foreign language lexical competence in strategic foreign language learning (communicative aspect)]. Naukovi zapysky Natsionalnoho universytetu «Ostrozhka akademiia», Seriia «Filolohiia» [Scientific Notes of the National University "Ostroh Academy", Series "Philology"], (62), 280–283. Retrieved from https://lingvj.oa.edu.ua/articles/2016/n62/103.pdf • Tymkova, (2023). Vykorystannia frazeolohizmiv na zaniattiakh z ukrainskoi movy yak neobkhidnyi element formuvannia movnoi kultury maibutnikh fakhivtsiv [Using phraseological units in Ukrainian language lessons as an essential element of future specialists’ linguistic culture formation]. International Science Journal of Education & Linguistics, 2(1), 69–76. Retrieved from https://www.researchgate.net/publication/367984956